Hegemoni Ideologi dalam Lirik Tembang Dolanan Sunan di Indonesia - Dian Karina Rachmawati; Dwiki Ayu Pramudya (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
Playing-songs (tembang dolanan) are songs for children as game accompaniment. This study aims to reveal the ideological hegemony contained in the lyrics of Sunan Giri playing-song and the moral leadership structure of Sunan Giri's character in preaching. The theory used is Hegemony by Gramsci and Metaphor by Pierce. This research used a qualitative description method. The reaearch object is the lyrics of Sunan Giri playing-song. The results of this study shows that the lyrics of Sunan Giri playing-song contains the hegemony of religious ideology. The concept of hegemony of ideology as outlined in the lyrics of